The redox-responsive transcriptional regulator Rex represses fermentative metabolism and is required for Listeria monocytogenes pathogenesis. - Cortney R Halsey (Public Library of Science (PLoS), 2021)
The Gram-positive bacterium Listeria monocytogenes is the causative agent of the foodborne disease listeriosis, one of the deadliest bacterial infections known. In order to cause disease, L. monocytogenes must properly coordinate its metabolic and virulence programs in response to rapidly changing environments within the host. However, the mechanisms by which L. monocytogenes senses and adapts to the many stressors encountered as it transits through the gastrointestinal (GI) tract and disseminates to peripheral organs are not well understood. In this study, we investigated the role of the redox-responsive transcriptional regulator Rex in L. monocytogenes growth and pathogenesis. Rex is a conserved canonical transcriptional repressor that monitors the intracellular redox state of the cell by sensing the ratio of reduced and oxidized nicotinamide adenine dinucleotides (NADH and NAD+, respectively). Here, we demonstrated that L. monocytogenes Rex represses fermentative metabolism and is therefore required for optimal growth in the presence of oxygen. We also show that in vitro, Rex represses the production of virulence factors required for survival and invasion of the GI tract, as a strain lacking rex was more resistant to acidified bile and invaded host cells better than wild type. Consistent with these results, Rex was dispensable for colonizing the GI tract and disseminating to peripheral organs in an oral listeriosis model of infection. However, Rex-dependent regulation was required for colonizing the spleen and liver, and L. monocytogenes lacking the Rex repressor were nearly sterilized from the gallbladder. Taken together, these results demonstrated that Rex functions as a repressor of fermentative metabolism and suggests a role for Rex-dependent regulation in L. monocytogenes pathogenesis. Importantly, the gallbladder is the bacterial reservoir during listeriosis, and our data suggest redox sensing and Rex-dependent regulation are necessary for bacterial survival and replication in this organ.